Large scale production of indole-3-acetic acid and evaluation of the inhibitory effect of indole-3-acetic acid on weed growth - Sakaoduoen Bunsangiam (Scientific Reports, 2021)
Abstract Indole-3-acetic acid (IAA) is the most common plant hormone of the auxin class and regulates various plant growth processes. The present study investigated IAA production by the basidiomycetous yeast Rhodosporidiobolus fluvialis DMKU-CP293 using the one-factor-at-a-time (OFAT) method and response surface methodology (RSM). IAA production was optimized in shake-flask culture using a cost-effective medium containing 4.5% crude glycerol, 2% CSL and 0.55% feed-grade l-tryptophan. The optimized medium resulted in a 3.3-fold improvement in IAA production and a 3.6-fold reduction in cost compared with those obtained with a non-optimized medium. Production was then scaled up to a 15-L bioreactor and to a pilot-scale (100-L) bioreactor based on the constant impeller tip speed (Vtip) strategy. By doing so, IAA was successfully produced at a concentration of 3569.32 mg/L at the pilot scale. To the best of our knowledge, this is the first report of pilot-scale IAA production by microorganisms. In addition, we evaluated the effect of crude IAA on weed growth. The results showed that weed (Cyperus rotundus L.) growth could be inhibited by 50 mg/L of crude IAA. IAA therefore has the potential to be developed as a herbicidal bioproduct to replace the chemical herbicides that have been banned in various countries, including Thailand.